ANTIMICROBIAL ACTIVITY OF TELANG LEAF EXTRACT AGAINST STAPHYLOCOCCUS AUREUS AND CANDIDA ALBICANS - Semi; Rustanti, Elly; Mudrikatin, Siti (Library Unit collaborates with the Institute for Research and Community Service, College of Health Sciences Husada Jombang, 2024)
Background: Infectious diseases that women often experience in obstetric cases are usually problems in the vaginal area, puerperal infections and some cases of infections of the reproductive organs. Efforts to reduce the negative impact of infection can be done by looking for compounds that have antimicrobial activity, one of which is Telang Leaf (Clitoria ternatea). Telang leaves contain flavonoids, flavanols, kaempferol, quercetin and mirisetin. From the results of various studies Telang Leaves have a pharmacological influence as an antimicrobial. Objectives: The purpose of this study was to determine the activity of telang leaf extract against the growth of Staphylococcus aureus bacteria and Candida albicans fungi based on the diameter of the inhibitory zone. Design: This research used experimental design. Methods: The research method used is experimental laboratories. The test was carried out by extracting Telang leaves by the maceration method, then evaporated with a rotary evaporator so that a concentrated extract was obtained. Extracts Made concentrations of 10%, 20%, 30%, 40% and 50%. The antimicrobial activity test of the extract against Staphylococcus aureus bacteria and candida albicans fungus was carried out by disc diffusion method. Results: The results showed that negative controls did not have an inhibitory zone diameter. The average diameter of the inhibition zone of telang leaf extract in Staphylococcus aureus is the highest with a concentration of 50%, which is 17.8 mm and a positive control of 42.6 mm. while in candida albicans fungus with a concentration of 50% with an inhibitory diameter of 16.5 mm and a positive control of 26.2 mm. Conclusion: The conclusion is that telang leaves have antimicrobial activity at a concentration of 50% against Staphylococcus aureus and candida albicans. So that, telang leaf extract can be developed as a treatment in infectious diseases in case of obstetrics.